Global Reporting Initiative Index Sebagai Model Pengukuran Triple Bottom Line Pada Industri Kategori Environment High Risk (Studi Komparasi Indonesia Dan Malaysia) - Gobel, Mohammad Rianto; Sayogo, Djoko Sigit; Prasetyo, Adi (Jurnal Reviu Akuntansi dan Keuangan)
This research aims to describe the parctice of Triple Bottom Line Disclosure to the industrieswhose the category is environment high risk in Indonesia and Malaysia which is reviewed byIndex Model GRI and explain the aspects that differ the practice of Triple Bottom Line Disclosure at environment high risk category in Indonesia and Malaysia which is reviewed by IndexGRI model. This research used Content Analysis and Mann-Whitney Test. The result of thisresearch shows that there are still many items of triple bottom line componen that have not beenshown yet.The significance of differences of Triple Bottom Line Disclosure about Malaysianindustry and Indonesia shows the point 64% from Indonesia and 36% from Malaysia and thereis some differencebetween Triple Bottom Line Disclosure of Malaysian industry and Indonesianindustry.Keywords: index GRI, TripleBottom Line, EnvironmentHigh Risk.